CAVITARY PNEUMONIA MIMICKING ASPERGILLOMA: A CASE REPORT - Supono, Effie Ang; Merari Panti, Astuti (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2025)
Pneumonia remains a significant global health burden. The 2015 Global Burden of Disease Study identified lower respiratory tract infections as the leading cause of death from infectious disease and the fifth leading cause of death overall. One of the potential complications of pneumonia is lung abscess formation. This paper aims to report and discuss a case of cavitary pneumonia in a 50-year-old male patient, which radiologically mimicked aspergilloma. A 50-year-old male presented to the Emergency Department of Bethesda Hospital, Yogyakarta, with complaints of hemoptysis ( 25 cc) and shortness of breath. Three days prior, he had completed an 8-day course of treatment for pneumonia at Tjitrowardojo Purworejo Hospital. Physical examination revealed anemia, dullness in the 3rd and 4th left intercostal spaces, and crackles in both lungs. Laboratory tests showed leukocytosis, neutrophilia, lymphopenia, and elevated C-reactive protein. Imaging revealed consolidation and a cavity with a crescent sign in the left lung. Biopsy did not reveal malignancy, bacteria, or fungi—only inflammatory cells. TB and HIV tests were negative. The patient was diagnosed with a lung abscess and treated with antibiotics (levofloxacin), antifungals (fluconazole), and antifibrinolytics (tranexamic acid). This case illustrates how a lung abscess can radiologically mimic an aspergilloma, particularly with the presence of a crescent sign on imaging. Accurate diagnosis relies on a combination of imaging, microbiologic testing, and clinical correlation. The patient responded well to pharmacological therapy during a 9-day hospitalization and follow-up.